Nonshared Environmental Influences on Academic Achievement at Age 16 - Kathryn Asbury; Nicola Moran; Robert Plomin (SAGE Publishing, 2016)
Twin studies find ~20% of the variance in achievement in public examinations taken at age 16 in the United Kingdom can be explained by experiences not shared within families. Nonshared environmental (NSE) influences, including measurement error, explain why monozygotic (MZ) twins differ from each other. Such influences work independently of genetic effects and may represent strong candidates for intervention. This study aimed to generate hypotheses about what these NSE factors might be. Perceptions of within-pair differences were gathered from n  = 497 pairs of MZ twins and their parents, and telephone interviews were conducted with n  = 56 families reporting different General Certificate of Secondary Education grades. "Environmental" explanations related to teacher quality, teacher-pupil relationships, and ability grouping. Families also explained discordance in terms of effort, interest, ability, and personality.